Linking Particle Semantic Roles in Hawrami Deverbal Noun Phrases - Jabbar Mirani; Hiwa Weisi; Farogh Mirani; Rafiq Shwani (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
Previous studies have focused mostly on the syntactic features of the linking particle (Ezafe) in simple noun phrases with little attention paid to its semantic representations and functions specifically within the context of deverbal noun phrases. The present study aims to analyze semantic functions of the linking particle as it appears between a deverbal noun and its various modifiers, and compare them with their corresponding elements in sentences in a Distributed Morphology framework (DM) in Hawrami. This study shows this ancient linker's trace in most Kurdish dialects exhibits agentive semantic functions in addition to expressing possession and modification. Furthermore, the subject of unaccusative verbs at the sentential level is realized as the patient/possessor or as the theme/possessor of their corresponding deverbal noun phrases. However, the subject of unergative verbs assumes the agentive/possessor role in their corresponding noun phrases. Moreover, the object of transitive and ditransitive verbs is represented as a patient or theme, and also as a possessed entity before the subject is realized as the possessor in the corresponding deverbal noun phrases. Results indicate that the representation of both sentences and their corresponding deverbal noun phrases within DM framework provides stronger support for a syntactic movement account of deverbal noun phrases, their semantic functions, and properties in Hawrami.